2019
DOI: 10.1016/j.yjmcc.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho-associated kinases suppresses cardiac myofibroblast function in engineered connective and heart muscle tissues

Abstract: Cardiac fibrosis is a hallmark of heart failure for which there is no effective pharmacological therapy. By genetic modification and in vivo inhibitor approaches it was suggested that the Rho-associated kinases (ROCK1 and ROCK2) are involved in pro-fibrotic signalling in cardiac fibroblasts and that they may serve as targets for anti-fibrotic therapies. We demonstrate that simultaneous inhibition of ROCK1 and ROCK2 strongly interfered with tissue formation and their biomechanical properties in a model of engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 79 publications
(96 reference statements)
2
16
0
Order By: Relevance
“…In this context, the inhibitory effect of ROCK inhibitors on stiffness was mediated by the regulation of lysyl oxidase, the collagen cross-linking enzyme and involved the activation of the actin-dependent MRTF/SRF pathway. This study also showed, that ROCK inhibitors similarly decreased stiffness of human engineered connective tissue and rat engineered cardiac muscle (Santos et al, 2019).…”
Section: Consequences Of Stiffness Changes On Cardiomyocyte Performancesupporting
confidence: 69%
See 1 more Smart Citation
“…In this context, the inhibitory effect of ROCK inhibitors on stiffness was mediated by the regulation of lysyl oxidase, the collagen cross-linking enzyme and involved the activation of the actin-dependent MRTF/SRF pathway. This study also showed, that ROCK inhibitors similarly decreased stiffness of human engineered connective tissue and rat engineered cardiac muscle (Santos et al, 2019).…”
Section: Consequences Of Stiffness Changes On Cardiomyocyte Performancesupporting
confidence: 69%
“…Santos et al utilized rat ring-shaped engineered connective tissue comprised of cardiac fibroblasts and collagen I while using ROCK signaling inhibitors. This resulted in reduced tissue stiffness, and also reduced TGF-β signaling-driven tissue stiffening (Santos et al, 2019). In this context, the inhibitory effect of ROCK inhibitors on stiffness was mediated by the regulation of lysyl oxidase, the collagen cross-linking enzyme and involved the activation of the actin-dependent MRTF/SRF pathway.…”
Section: Consequences Of Stiffness Changes On Cardiomyocyte Performancementioning
confidence: 99%
“…Fasudil, a selective inhibitor for the RhoA-ROCK pathway, has been used in clinic as a vasodilator [18,19,20] and for RhoA-mediated functional studies [21,22,23]. We previously reported that fasudil can partially block Th2 differentiation and OVA-induced allergic airway inflammation [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is also applied in patients with pulmonary hypertension [19], diabetic patients with left ventricular diastolic dysfunction [20], etc. For RhoA functional research, fasudil has been applied for fibrosis therapy in several models [21,22,23]. Fasudil may also inhibit Th17 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the strong anti-fibrotic potential of the pharmacological inhibition of ROCK is in part due to a decrease in the expression of LOX. Indeed, in a model of engineered connective tissue, composed by cardiac fibroblasts and collagen, Rho-associated kinases (ROCK1 and ROCK2) were identified as key mediators of TGF-β-dependent tissue stiffening of engineered heart muscle tissue, and LOX as a downstream target of this ROCK-actin-MRTF/SRF pro-fibrotic signaling pathway [94].…”
Section: Lox/loxls As Pharmacological Targets In Myocardial Diseasesmentioning
confidence: 99%